A Good Example of Peaceful Coexistence? The Soviet Union, Austria, and Neutrality, 1955-1991 - Mueller, Wolfgang (Zentraleuropa-Studien, 2011)
This monograph, based on newly declassified sources from Western and Russian archives as well as on communist texts about international law and neutrality, is the first English-language account of Soviet policy towards neutral yet capitalist Austria during the Cold War. In order to make neutrality a model for the West, the Kremlin presented the unique Soviet-Austrian relationship as "a good example of peaceful coexistence" and a showcase for the benefits a Western state might reap by declaring neutrality. This honor, however, had strings attached: The communist doctrine of neutrality contained obligations that were expected to make it possible to exploit neutral states as instruments of Soviet policy and bring them nearer the socialist bloc.